The Principle of Contradiction. - Conze, Edward (Lexington Books (R and L) : Lexington Books, 2016)
Heine introduces The Principle of Contradiction in its first English translation. Conze's account of the history and evolution of the principle of contradiction illuminates the thought of Aristotle, Marx, and Buddha, and provides the groundwork for a new cross-cultural and interdisciplinary approach to philosophical theory and practice.